Complex Formation of Tetramethyltetraaza-14-crown-4 with Iodine - MOATAMEDI, OMID; REZA FIROOZ, ALI; SEMNANI, ABOLFAZL; GHADERI, BAHARE; PARVANAK, KAVEH (Asian Journal of Chemistry, 2010)
Spectrophotometric and conductometric study concerning the interaction between tetramethyl-tetraaza-14-crown-4 (TMTA14C4) and iodine has been performed in dichloromethane at 25 ºC .The results are indicative of the formation of (macrocycle)2I+. I3– sandwich complex through equilibrium reaction. The conductometric data confirm the proposed adduct and show that the products are somewhat as free ions. The stability constant of the complex is obtained by fitting the absorbance vs. mole ratio data in MATLAB program. The oscillator strength (f) and the transition probability (μ) of the charge-transfer bands and ionization potential (IP) of donor have been calculated from the spectral data. IR spectra of pure macrocycle are compared with the corresponding iodine complex and the effect of complexation on absorption bands is discussed. The comparisons of result with the similar ones in chloroform are indicative of the formation of macrocycle. I+. I3– in recent solvent. The different stoichiometries in two solvents are assigned to specific interaction between solventmacrocycle and different physical properties of the solvents.